Stability Analysis of Steep Bank River Slope with Clay Type in Amphibile Vehicle Landing - Akil Suwandi; Gita Amperiawan; Susilo Adi Purwantoro; Sovian Aritonang (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
In river crossing operations using amphibious vehicles, the landing process is a critical point for the success of the operation. This study aims to obtain an overview of the potential failure of amphibious vehicles during landing due to the stability factor of the slope / slope caused by topographic conditions in the form of steep bank slopes and geological conditions in the form of poor soil bearing capacity. This study begins with observations on one of the rivers to obtain an overview of the presence of steep riverbanks, followed by a literature study on an amphibious vehicle, and observations of the landing process of an amphibious vehicle in training activities at the Gedebage reservoir, Bandung. This study obtains an illustration that there is an area in the watershed (DAS) with steep geometric shapes on its banks, which becomes an obstacle in the amphibious vehicle landing operation which will be found during the operation. Another illustration is when the steep banks of the river have low soil bearing capacity, there will be a potential failure of amphibious vehicles to land due to the collapse of the river bank slopes.